2016
DOI: 10.3390/ijerph13030274
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the Multivariate Linear Mixed Model to the Analysis of Shoulder Complexity in Breast Cancer Patients

Abstract: In this study, four major muscles acting on the scapula were investigated in patients who had been treated in the last six years for unilateral carcinoma of the breast. Muscle activity was assessed by electromyography during abduction and adduction of the affected and unaffected arms. The main principal aim of the study was to compare shoulder muscle activity in the affected and unaffected shoulder during elevation of the arm. A multivariate linear mixed model was introduced and applied to address the principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Even with normal pain‐free motion of the arm and shoulder, in the scapulothoracic, glenohumeral, acromioclavicular, and sternoclavicular joints, patients may encounter another issue, namely muscle lower muscle electrical activity. Some studies suggest that humeral elevation of the arm, upward movement on the affected side, and left shoulder movement will increase the electrical activity of all four muscles regardless of which side is affected, while treatment with wide local excision and chemotherapy is associated with generally decreased electrical activities . In our study, implant‐based and TRAM flap reconstruction did not affect shoulder muscle strength.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Even with normal pain‐free motion of the arm and shoulder, in the scapulothoracic, glenohumeral, acromioclavicular, and sternoclavicular joints, patients may encounter another issue, namely muscle lower muscle electrical activity. Some studies suggest that humeral elevation of the arm, upward movement on the affected side, and left shoulder movement will increase the electrical activity of all four muscles regardless of which side is affected, while treatment with wide local excision and chemotherapy is associated with generally decreased electrical activities . In our study, implant‐based and TRAM flap reconstruction did not affect shoulder muscle strength.…”
Section: Discussionsupporting
confidence: 43%
“…Forthomme et al found decreased muscle strength after an LD flap in a comparison of the isokinetic test results for different shoulder muscles. Oskrochi et al investigated shoulder muscle activities by SEMG to analyze shoulder complexity in breast cancer patients. In our study, shoulder complexity after breast cancer was assessed by both SEMG and measurement of the ROM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We fitted the mixed linear model [ 24 , 25 ] using the SAS PROC MIXED procedure to analyse the impact factors of KAP. The variables of interest included educational reform, gender, the number of communities that the student joined during the undergraduate experience (hereinafter, community number), self-perceived character, registered permanent residence, parents’ literacy, Internet age, and hours spent online per day.…”
Section: Methodsmentioning
confidence: 99%